Development and validation of a scale to capture social desirability in food safety culture. (December 2017) - Jespersen, Lone; MacLaurin, Tanya; Vlerick, Peter
Abstract: The evaluation of food safety culture in a food company is influenced by human factors such as employees' tendency to respond to social desirability – a reflection of respondents' tendency to answer questions in a manner that will be viewed favorably by others. Building on previous research a self-assessment scale consisting of 18-statements (FSDRS) was developed to capture desirable responding in food safety. Statistical analyses of data collected from 816 North-American food manufacturing professionals revealed that a shortened 14-item version of the FSDRS scale provides a reliable and valid measurement of the extent to which employees deceive themselves. It is concluded that the proposed FSDRS will enrich food safety culture measurement and food safety performance. Highlights: Impact of the human factor - social desirability - answering questions to be viewed favorably by others, on food safety. An ecological social desirability scale adapted to the food safety domain. Empirical study captured magnitude of social desirability in five North American food companies. Considered social desirability as a control factor in food safety research. Contextualized food safety by measurement of social desirability.